Bendable thermoelectric generators composed of p- and n-type silver chalcogenide nanoparticle thin films. (July 2018) - Yang, Seunggen; Cho, Kyoungah; Park, Yoonbeom; Kim, Sangsig
Abstract: In this study, we design and construct lateral thermoelectric generators on bendable substrates with pairs of p -Ag2 Te and n -Ag2 Se chalcogenide nanoparticle (NP) thin films, and investigate their thermoelectric performances in ambient atmosphere. The individual Seebeck coefficient and lateral thermal conductivity are 1110 μV/K and 0.67 W/m K, respectively, for a single p -Ag2 Te thin film, and − 290 μV/K and 0.55 W/m K, respectively, for a single n -Ag2 Se NP thin film. A ring-shaped thermoelectric generator made with 50 pn modules of these NP thin films at a temperature difference of 15 K generates a Seebeck voltage of 1.16 V and an output power of 106 mW/cm 2 . Moreover, the mechanical durability of our thermoelectric generator is verified by repeated bending tests of up to 5000 cycles. Graphical abstract: The bendable thermoelectric generator generates Seebeck voltage of 1.16 V at a temperature difference of 15 K for 50- pn pairs composed of p -Ag2 Te and n -Ag2 Se nanoparticle thin films. fx1 Highlights: Lateral thermoelectric generator is constructed with nanoparticle thin films. Thermoelectric performances are evaluated at the small temperature gradients of 15 K. The Seebeck voltage of 1.16 V is generated for the 50- pn pairs. The thermoelectric generator exhibits superior mechanical stability.